Chemosensory detection of aversive concentrations of ammonia and basic volatile amines in insects. - Clark, J.T.; Ganguly, A.; Ejercito, J.; Luy, M.; Dahanukar, A.; Ray, A. (iScience, 2023)
Basic volatiles like ammonia are found in insect environments, and at high concentrations cause an atypical action potential burst, followed by inhibition in multiple classes of olfactory receptor neurons (ORNs) in Drosophila melanogaster. During the period of inhibition, ORNs are unable to fire action potentials to their ligands but continue to display receptor potentials. An increase in calcium is also observed in antennal cells of Drosophila and Aedes aegypti. In the gustatory system, ammonia inhibits sugar and salt responses in a dose-dependent manner. Other amines show similar effects in both gustatory and olfactory neurons, correlated with basicity. The concentrations that inhibit neurons reduce proboscis extension to sucrose in Drosophila. In Aedes, a brief exposure to volatile ammonia abolishes attraction to human skin odor for several minutes. These findings reveal an effect that prevents detection of attractive ligands in the olfactory and gustatory systems and has potential in insect control.